PENGARUH MOTIVASI MENGHINDARI RIBA DAN PRODUCT KNOWLEDGE PERBANKAN SYARI’AH TERHADAP KEPUTUSAN MENJADI NASABAH PT. BANK SYARI’AH MANDIRI PASURUAN- JAWA TIMUR - Imam Wahyudhi (EL MUDHORIB : Jurnal Kajian Ekonomi dan Perbankan Syariah, 2022)
An islamic bank (a sharia bank) is a financial institution functioning as a financial intermediary based on Islamic sharia principles. The factor of obedience with sharia principles and knowledge of financial products are the main factors for consideration for sharia customers. Decreasing in the number of customers for two consecutive years at Bank Syariáh Mandiri Pasuruan becomes temporary concern while Pasuruan City is well known as the city of Muslim students.This research is a quantitive descriptive study using accidental sampling technique. Research will describe the state of the field wich aims to answer the question wether there is a significant effect simultaneously and partially between the independet variable and dependent variable.The results obtained indicate that the motivation to avoid usury and knowledge of banking products simultaneously on the decision to become a customer does not have a positive and significant effect with the proportion of motivation tp avoid usury (x1) and knowledge of sharia banking products (x2) on the decision to become a customer (Y) amounted to 24.7%. Meanwhile, the variable partial test (x1) has no positive effect. For variable (x2) has a significant effect.